Caffeine stimulates ventilation in athletes with exercise-induced hypoxemia - Chapman, R. F.; Stager, J. M. (Medicine & Science in Sports & Exercise, 2008)
Introduction/Purpose: Many athletes with exercise-induced hypoxemia (EIH) show an insufficient ventilatory response to exercise and low resting ventilatory responsiveness. The purpose of this project was to determine whether a moderate dosage of caffeine, a common ventilatory stimulant, could augment resting ventilatory responsiveness, exercise ventilation (VE), end-tidal O2 partial pressure (PetO2), and arterial oxyhemoglobin saturation (HbSaO2) in athletes with EIH.